Penerapan Multimedia Interaktif Powerpoint Untuk Meningkatkan Minat dan Hasil Belajar Tematik Muatan IPA Siswa SD - Deni Putri Widyaningrum; Heri Maria Zulfiati; Milatun Nisa (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
This classroom action research aims to determine the increase in student interest and learning outcomes through the application of interactive multimedia PowerPoint to thematic learning of science content for fourth grade students at SDN Wonosari 01. Data collection on student interest in learning uses observation and questionnaire methods, while data on student learning outcomes through science test methods. The results showed that the application of interactive multimedia PowerPoint in thematic learning of science content could increase interest and learning outcomes. The increase in student interest in learning can be seen from the average acquisition of interest in learning obtained by students in the pre-action of 40.82 (low category) with the percentage of students who get a score of 45 as much as 38%, in the first cycle of 44.71 (enough category) with the percentage of students who get a score of 45 is 58%, and in the second cycle 49.03 (high category) with the percentage of students who get a score of 45 as much as 81%. Student learning outcomes in pre-action obtained an average of 66.11 with students completing or achieving KKM as much as 42.30%, the first cycle of 69.23 where students who completed as many as 65.38%, and the second cycle of 75.64 with students completed as many as 80.76% of the total number of students. Based on these data, with the application of interactive multimedia PowerPoint, it can be concluded that interest in thematic learning of science content can improve student learning outcomes.